A Study on the Influence of Sand Median Grain Size on the Short-Term Recovery Process of Shorelines - Lim, Changbin; Kim, Tae-Kon; Kim, Jong-Beom; Lee, Jung-Lyul (Frontiers in Marine Science, 2022)
Recently, the impacts of short-term erosion caused by storm wave on coastal damage are increasingly recognized as social issues, compared to those of long-term erosion from climate change or coastal development. The erosion caused by the storm wave has an episodic characteristic that the shoreline recovers gradually after retreating for a short-term. And if shoreline changes caused by longshore sediment transport are not taken into consideration, the shoreline position is determined by following two physical parameters based on the bulk response model. The beach response factor determines converging ultimate erosion on the assumption that incident wave constantly affect a beach, which can be estimated according to the concept of Dean's profile. On the contrary, the beach recovery factor affects the velocity of the shoreline retreat and recovery. Therefore, the parameter plays an important role to predict the peak erosion due to the storms. However, there are still insufficient research to utilize it as an engineering design for erosion reduction. In this study, the two methodologies (i.e., approximation formula and statistical analysis) that estimates peak erosion width caused by the storms are compared to extract the beach recovery factor. During the process, it is confirmed that peak wave height has little impacts on the beach recovery factor. Rather, it is mainly determined by the median grain size. Also, the beach recovery factor is estimated as a function of median grain size based on the shoreline and sand survey data conducted over 10 years. Among the 41 surveyed sites along the east coast, 11 sites of straight-type shorelines that directly react with the incident wave were applied to consider only the short-term recovery process. To prove validity, estimated factor was applied into the real sea and then the results were compared to the shoreline data extracted from CCTV images. Using these results, the peak erosion width for a target wave event can be predicted with only median grain size. This study results are expected to be used as a concrete and practical means to manage the coast, in preparation for the current and future shoreline erosion threats.